Simulasi Kinerja Termodinamika Refrigerator Dengan Injeksi Cairan Menggunakan R515A Dan R515B - Amalo, Alexander C.; Gurnawati, Gurnawati; Dwinanto, Matheus Magnus (Universitas Nusa Cendana, 2024)
This research aims to analyze and compare the thermodynamic performance of refrigerators using two types of refrigerants, namely R515A and R515B, with liquid injection techniques. Refrigerators are important devices in a variety of applications, including the food, pharmaceutical, and household refrigeration industries. This simulation includes important variables such as pressure, temperature, mass flow, and thermophysical properties of both refrigerants. In addition, it also considers fluid injection technique variables such as injection amount, injection time, and injected fluid properties. The research results show a performance comparison between R515A and R515B in terms of thermal efficiency, cooling capacity, and power consumption. It was found that the use of R515B with certain liquid injection resulted in a significant increase in the overall efficiency of the refrigerator system. The results show that proper setting of the injection amount and injection time can optimize the performance of the refrigerator system. Selecting the right refrigerant and liquid injection strategy can produce a more efficient system. This research provides in-depth insight into the thermodynamic aspects of refrigerator systems and illustrates the importance of refrigerant selection and operational techniques in achieving maximum efficiency.